An Analysis of Grammatical Cohesion of Reading Texts in "Paragraph Writing" Textbook - Artarifah, Fitriani; Baharuddin; Arafiq; Wardana, Lalu Ali; Sahrul (Journal of English Education Forum (JEEF), 2024)
This study aims to find out the types of grammatical cohesion in the reading texts in “Paragraph Writing” textbook. The data were the reading texts taken from a textbook entitled “Paragraph Writing” and analyzed using the theory proposed by Halliday & Hasan (1976). This study uses a qualitative approach with a descriptive qualitative design and documentary technique as data collection procedures. The findings show that all types of grammatical cohesion are found in the total 22 reading texts. From 211 sentences, 569 data are classified as grammatical cohesion items and all types of it are found. The reference occurs 442 times, ellipsis 17 times, substitution only once, and conjunction 109 times. To sum up, “Paragraph Writing” Textbook is a good supplementary teaching material for lecturers in teaching grammatical cohesion, and a suitable additional learning material for students in mastering discourse analysis, especially the grammatical cohesion.